DEGRADING COMMONS: THE ECOLOGICAL CONSEQUENCES OF MIGRATION- THE CASE OF KERALA, INDIA IN A HISTORICAL PERSPECTIVE - V. P. RAGHAVAN
Kerala Migration becomes a socio-economic phenomenon of Kerala. The peasant farmers in the central region of called Travancore have massively moved to the northern region of Kerala called Malabar in 1920s and continued till 1960s. Migration opens opportunities, but they also pose problems like economic, cultural demographic and environmental. The present study examines the environmental impacts of peasant migration from Travancore to Malabar on the rural economy of the region of destination in a historical perspective.